Endothelial Heparan Sulfate Proteoglycans in Sepsis: The Role of the Glycocalyx - Oshima, Kaori; King, Samantha I.; McMurtry, Sarah A.; Schmidt, Eric P. (Seminars in Thrombosis and Hemostasis, 2021)
There is increasing recognition of the importance of the endothelial glycocalyx and its in vivo manifestation, the endothelial surface layer, in vascular homeostasis. Heparan sulfate proteoglycans (HSPGs) are a major structural constituent of the endothelial glycocalyx and serve to regulate vascular permeability, microcirculatory tone, leukocyte and platelet adhesion, and hemostasis. During sepsis, endothelial HSPGs are shed through the induction of “sheddases” such as heparanase and matrix metalloproteinases, leading to loss of glycocalyx integrity and consequent vascular dysfunction. Less well recognized is that glycocalyx degradation releases HSPG fragments into the circulation, which can shape the systemic consequences of sepsis. In this review, we will discuss (1) the normal, homeostatic functions of HSPGs within the endothelial glycocalyx, (2) the pathological changes in HSPGs during sepsis and their consequences on the local vascular bed, and (3) the systemic consequences of HSPG degradation. In doing so, we will identify potential therapeutic targets to improve vascular function during sepsis as well as highlight key areas of uncertainty that require further mechanistic investigation.
Keywords: endothelial glycocalyx; sepsis; heparan sulfate proteoglycans